The Concept of Local Economic Development Based on Circular Economic Specialization and Integrated Governance - Sanjaya, Ahmad Rifal Ari (IDFoS Indonesia, 2022)
This research aimed to outline the concept of Local Economic Development (LED), which aimed to address development issues, particularly in overcoming regional disparities and poverty. The research method used was qualitative. The results showed that the concept of LED was aimed at empowering all stakeholders, including communities, businesses, and governments, to collaborate and participate in economic activities and development. It adhered to the principles of circulation, integration, and sustainability. In this concept, the development of regions occured in three stages. It involved developing peripheral or underdeveloped regions with the assistance of advanced or core regions by providing resources so that previously underdeveloped areas could become advanced and prosperous. This led to the realization of integrated and competitive regions without disparities. The governance developed in this concept was Integrated, while the economic system developed was Circular Economy Specialization, which was based on a circular and sustainable economic system that renews and restores while considering social foundations and ecological limits.